2016
DOI: 10.1002/jez.2035
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Profile, Biological Activities, and Toxic Effects of Proteins in the Rhinella schneideri Parotoid Gland Secretion

Abstract: Parotoid glands of amphibians are known for the production of several biologically active compounds having pharmacological and toxic effects in mammals. In the present work, a protein fraction obtained from Rhinella schneideri parotoid gland (RsPP) was characterized to study its biological and toxic effects. Rhinella schneideri parotoid secretion is composed of up to 30% (w/w) of soluble proteins. Tandem mass spectrometric analysis of the RsPP identified 104 proteins, including actin, beta-actin, ribosomal pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 40 publications
5
16
0
Order By: Relevance
“…Similar to a previous work regarding the anuran R. schneideri parotoid secretion [46], our results showed that A. siemersi skin secretion exerted no pro-coagulant activity. Likewise, no proteolytic or amidolytic activities were detected in the secretion of Argentine frog skin.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to a previous work regarding the anuran R. schneideri parotoid secretion [46], our results showed that A. siemersi skin secretion exerted no pro-coagulant activity. Likewise, no proteolytic or amidolytic activities were detected in the secretion of Argentine frog skin.…”
Section: Discussionsupporting
confidence: 91%
“…Although many papers have described the morphology of amphibian poison glands since the nineteenth century [ 23 26 ], none of them invested in an integrative approach, trying to gather morphological data with the amphibian biology and natural history [ 13 ]. More recently, some studies have examined these glands in an interdisciplinary context, in order to increase the understanding of the morphology, biochemistry, and functioning of these structures [ 5 , 6 , 12 , 13 , 15 , 22 , 27 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the large size of the individual glands that compose the parotoids, these cutaneous organs can synthesize and store significant large amounts of poison used in chemical defence against predators [ 3 , 5 ]. In toads in general, the secretion is composed of a mixture of steroids, biogenic amines and proteins, as well as mucus [ 3 , 5 , 10 , 14 , 15 ]. If ingested, toad skin secretion may cause death of several vertebrates, including humans [ 16 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zelnik, Ziti and Guimarães 14 made a chromatographic study of the bufadienolides isolated from the poison of the parotid glands of Bufo paracnemis (former R. schneideri ) Lutz 1925 and identified the compounds: γ-sitosterol, argentinogenin, bufalin, bufotalinin, gamabufotalin, hellebrigenin, hellebrigenol, resibufogenin and telocinobufogenin. But few studies have described the isolation and biological effects of molecules of the R. schneideri poison, 6 , 7 , 15 and there is limited information about identification of substances from toad poison, as well as, their pharmacological activities. Among them, Anjolette et al 6 isolated and partially characterized the function and structure of the first bufadienolide (6,000 Da) with inhibitory action over chymotrypsin, isolated from R. schneideri poison.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, Anjolette et al 6 isolated and partially characterized the function and structure of the first bufadienolide (6,000 Da) with inhibitory action over chymotrypsin, isolated from R. schneideri poison. Souza-Filho et al 15 isolated a galectin, from R. schneideri poison, that presented an anti-inflammatory activity and slight toxic effects in mice.…”
Section: Discussionmentioning
confidence: 99%